Analysis of the Capacity of Prison Security Structures on Inmate Escape Prevention in Nakuru Main Prison, Kenya. A Perspective of Junior Prison Officer’s - Rono, Joash Kiprotich; Mwangi, Samson Wokabi; Omboto, John (Advances in Social Sciences Research Journal, 2020)
This study attempts to analyze the capacity of prisons security structures in Nakuru main prison to prevent inmate’s escapes in the perspective of junior officers working in the institution who formed 80 % of the sample respondents in the study. This research adopted descriptive research design which involved the use of observation, case study approach and survey technique. Data was collected majorly using questionnaires as data collection instruments and was self-administered to 142 junior prison officers who were directly involved in the facilitation of safe custody to prisoners in Nakuru main prisons. The observation checklist was also used to ascertain the state of the physical security infrastructure used to prevent escapes in Nakuru main prison. Data obtained was analyzed using statistical package for social sciences (SPSS) and presented using frequencies, pie charts and tables. The findings from the majority of the respondents showed a lack of permanent perimeter fence at 47.4 %, old dilapidated buildings at 28.9%, lack of the use of technology e.g CCTV at 19.7%, inadequate lighting system at14.5%. The study recommendsconstruction of a modern security wall in the institution as a strategy to effectively prevent escapes, use of new technology e.g CCTV erection of a proper and adequate watchtowers/Sentries and provision of adequate lighting system at Nakuru main prisons. In addition, there is a need to escalate a similar study to all prison institutions in order to enrich the findings and recommendations for Policymakers in the criminal justice system.